Multifunctional nitrogen and boron co-doped carbon dots: A fluorescent probe for Hg2+ and biothiol detection with bioimaging and antifungal applications - Wang Jie; Ma Huihui; Zhang Chunjing; Hu Yue; Wang Qi; Zhao Xuesong; Liu Xi; Liu Zhenyan; Yi Tonghui (Open Chemistry)
Nitrogen and boron co-doped carbon dots were synthesized using boric acid and triammonium citrate as precursors. N,B-CDs are effective in detecting both mercury ions and biothiols. The linear detection range of mercury ion and biothiols is 0–150 and 0–100 μmol/L, respectively. The detection limit for mercury ions is 18 nmol/L, and for the three kinds of biothiols, it is 13.42, 23.13, and 28.74 nmol/L, respectively. N,B-CDs have proven effective for detecting both in tap water and in human serum samples. N,B-CDs have low cytotoxicity and can be used for HeLa cell imaging. Beyond their detection capabilities, N,B-CDs also possess antifungal activity, effectively eliminating Cryptococcus neoformans and Candida albicans. The findings indicate that N,B-CDs could be used as multifunctional probes for cellular labeling and hold potential in the development of antifungal drugs.